Accounting conservatism in the face of economic policy uncertainty in GCC countries - Alkhalaileh, Ashraf Hamad Rizik; Abdul Hamid, Mohamad Ali; Saidin, Saidatunur Fauzi; Khan, Faisal (Czestochowa University of Technology, 2024)
Economic policy uncertainty (EPU) significantly influences decision-making in corporate and financial spheres globally. The challenging economic landscape in the Gulf Cooperation Council (GCC) countries adds complexity to financial reporting. The primary objective of this study is to investigate the impact of EPU on accounting conservatism in non-financial firms listed in the GCC. It also aims to unearth whether higher levels of EPU lead to more conservative accounting practices among these firms. Furthermore, the study explores the moderating effect of corporate governance between EPU and accounting conservatism. Hence, this study particularly focuses on the unique challenges posed by the economic landscape in GCC. Utilizing data from GCC-listed non-financial firms from 2010 to 2022, the research employs the dynamic Generalized Method of Moment (GMM) estimation for robust analysis of causal relationships in panel data. This rigorous methodology permits the inspection of both the short-term and long-term impacts of EPU on accounting conservatism while accounting for potential endogeneity and dynamic effects in the data. In addition, the study integrates measures of corporate governance to explore its moderating effect on the relationship between EPU and accounting conservatism. The findings reveal that EPU has a significant positive impact on accounting conservatism. Moreover, corporate governance significantly moderates the region's association between EPU and accounting conservatism. The research underscores the need for targeted policy approaches in the GCC region to address the impact of EPU on accounting conservatism. It advocates for legal frameworks that support cautious accounting practices, enhancing financial stability and transparency, particularly during uncertain economic periods.